The understanding of the terms “public health” and “public health policy” and their legal implications. Gloss to the judgment of the European Court of Human Rights of April 21, 2021 (VAVŘIČKA et al. v. Czech Republic) - Czechowicz, Sebastian (Studia Iuridica Toruniensia, 2025)
The gloss deals with a ruling of the European Court of Human Rights, which is the finale of the consideration of several combined complaints against the Czech Republic regarding the operative obligation of vaccination. However, this ruling emphasized the importance of the supra-individual legal good, which is public health. In addition, it pointed to the obligation to carry out public health policies. These terms, however, were not defined. These aspects are dogmatically and practically momentous, which justifies an attempt to clarify them. This commentary appreciates this non-obvious aspect undertaken by the Court. The gloss fully approves of the findings made by the ECHR.